2018
DOI: 10.1111/pde.13562
|View full text |Cite
|
Sign up to set email alerts
|

Itching at night: A review on reducing nocturnal pruritus in children

Abstract: The most common causes of chronic nocturnal itching in children are atopic dermatitis and psoriasis, with lichen simplex chronicus and prurigo nodularis contributing to lesser degrees. Despite the prevalence of nocturnal itching, its pathophysiology remains poorly understood. The most troubling consequence of itching at night is poor quality of sleep. Poor sleep quality in children with nocturnal itching has been linked to adverse neurocognitive, behavioral, and physiologic outcomes, including poor performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A recent Cochrane Review concluded that there is no consistent evidence for the effectiveness of oral H1 antihistamines 133 . Sedating H1 antihistamines may be tried for a short period in acute exacerbations, when sleep disturbances persist despite TCS and emollient use, 270 but long‐term use is not recommended.…”
Section: Specific Considerations For Childrenmentioning
confidence: 99%
“…A recent Cochrane Review concluded that there is no consistent evidence for the effectiveness of oral H1 antihistamines 133 . Sedating H1 antihistamines may be tried for a short period in acute exacerbations, when sleep disturbances persist despite TCS and emollient use, 270 but long‐term use is not recommended.…”
Section: Specific Considerations For Childrenmentioning
confidence: 99%
“…not reach consensus, with only 47% of the panelists scoring for agreement. The heterogeneous presentation of AD at diagnosis also applied to risk factors; a lack of consensus regarding the presence of nonatopic comorbidities has been identified elsewhere [5,22]. Such comorbities include psychological disorders and lifestyle behaviors associated with high cardiovascular risk.…”
Section: From Symptoms To Diagnosismentioning
confidence: 99%
“…However, no consensus was reached regarding the utilization of an AD school or educational measures to improve specific outcomes such as sleep quality or itching management. The relevance of these educational measures is increasingly being acknowledged, particularly in childhood, where nocturnal itching-and the subsequent sleep disturbance-may affect cognitive development [22].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several antidepressants have also shown some benefits in treating itch [30][31][32]. Khanna et al performed a systematic review to of the current literature to summarize the efficacy of mirtazapine, a tetracyclic antidepressant, in treating chronic itch [33].…”
Section: Treatmentmentioning
confidence: 99%